PERAN CITRA MEREK DAN LOKASI TERHADAP EKSISTENSI BANK NEGARA INDONESIA DI UNIVERSITAS PEDIDIKAN INDONESIA - Nur Cahayu Baitunnisa; Melih Nurasobah; Naila Nur Nafisah Syarif; Nawfal Muhammad Fattan; Raehani Liviana Syahrani; Buyung Firmansyah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Many companies, one of which is from the banking sector, collaborate with universities to improve the company's image, attract new customers and maintain the company's existence. The elimination of Automated Teller Machines (ATMs) plus physical Student Identity Cards (KTM) at the Indonesian Education University (UPI) is considered to affect the existence of Bank Negara Indonesia (BNI) at UPI. This study aims to describe the role of brand image and location on BNI's existence from the perspective of new students of the Faculty of Economics and Business Education (FPEB) UPI. The data collection technique used interviews with 25 interviewees who were FPEB students class of 2023. The data analysis method uses data reduction, data presentation, and conclusion drawing. The results showed that Brand Image has a role in BNI's existence, while Location does not have a significant role in BNI's existence. However, the elimination of KTM plus physical ATMs that previously cooperated with BNI is enough to affect students' knowledge of BNI at UPI. It was found that the lack of information and access to location can affect BNI's existence at UPI. This is unlike when KTM was still in physical form which made students visit the branch office at least once.